2019
DOI: 10.5812/sdme.64668
|View full text |Cite
|
Sign up to set email alerts
|

Design, Implementation, and Evaluation of a Medical Education Fellowship Program for the Faculty Members of Kerman University of Medical Sciences Based on the Kirkpatrick Model

Abstract: Background: Attempts to increase the development of faculty members can improve their ability to assume different roles. Objectives: The purpose of this study was to design, implementation, and evaluation a medical education fellowship program for the faculty members of Kerman University of Medical Sciences and to propose practical recommendations for the future design of development programs. Methods: In this semi-experimental study, a total of 53 faculty members of Kerman University of Medical Sciences parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(23 reference statements)
2
2
0
1
Order By: Relevance
“…This improvement is similar to the findings reported in previous studies, like results shown in the different studies held by El Naggar et al (2013) 39 and Abdel Nasser et al (2018) 24 , where pre-test and post-test showed a statistically significant difference between the results of the pre-and post-test score (p ≤ 0.05). Similar results were documented in another study held by Dehghani MR et al (2019) to measure the second level of the Kirkpatrick model, they defined and compared the knowledge of faculty members in the pre-test and post-test. The results showed a significant increase in the participants' knowledge from the pre-test (mean score, 9.9 out of 20) to post-test (mean score, 13.9 out of 20), based on the results of the t-test; this finding confirms the positive effects of the FDP on participants' acquisition of knowledge 40 .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This improvement is similar to the findings reported in previous studies, like results shown in the different studies held by El Naggar et al (2013) 39 and Abdel Nasser et al (2018) 24 , where pre-test and post-test showed a statistically significant difference between the results of the pre-and post-test score (p ≤ 0.05). Similar results were documented in another study held by Dehghani MR et al (2019) to measure the second level of the Kirkpatrick model, they defined and compared the knowledge of faculty members in the pre-test and post-test. The results showed a significant increase in the participants' knowledge from the pre-test (mean score, 9.9 out of 20) to post-test (mean score, 13.9 out of 20), based on the results of the t-test; this finding confirms the positive effects of the FDP on participants' acquisition of knowledge 40 .…”
Section: Discussionsupporting
confidence: 70%
“…Similar results were documented in another study held by Dehghani MR et al (2019) to measure the second level of the Kirkpatrick model, they defined and compared the knowledge of faculty members in the pre-test and post-test. The results showed a significant increase in the participants' knowledge from the pre-test (mean score, 9.9 out of 20) to post-test (mean score, 13.9 out of 20), based on the results of the t-test; this finding confirms the positive effects of the FDP on participants' acquisition of knowledge 40 .…”
Section: Discussionsupporting
confidence: 70%
“…A combination of student-centered and teacher-centered methods including lecture, problem-based learning, team work, projects, question and answer, discussions in small groups, e-learning, and virtual education was applied to deliver the courses. [ 19 ]…”
Section: Methodsmentioning
confidence: 99%
“…(3) Los programas académicos en el área de salud bien planificados, proporcionan conocimientos integrales actualizados y dan confianza a los profesores, lo que resulta en una actitud más positiva y creen en la autoeficiencia para mejorar el aprendizaje, generando una alta satisfacción al equipo participante y docente. (12,13,14,15) En metodologías de enseñanza basada en simulación, el rol de instructor constituye dentro del proceso de aprendizaje un facilitador clave que llevará al logro de los objetivos de aprendizaje, (16,17,18,19) por lo que su entrenamiento resulta sumamente imprescindible, especialmente donde para dejar de lado el rol clásico de docente poseedor de conocimiento. De acuerdo con Rojo y Díaz, el docente en Simulación debe ser formado para: 1.-Elaborar y diseñar los escenarios de una forma realista, centrados siempre en que en ellos, los alumnos puedan explorar distintas habilidades que los conduzcan a conseguir los objetivos de aprendizaje.…”
Section: Introductionunclassified